NILAI-NILAI PENDIDIKAN AKIDAH DALAM KITAB AL BARZANJI KARYA SYAIKH JA’FAR AL BARZANJI - Nurhalimah Rangkuti; Nunu Burhanuddin Nunu; Iswantir Iswantir; Nur Hidayah Dayah (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
The research discusses the education of faith in the book of Al Barzanji by Sheikh Ja'far Al Barzanji, as well as its relevance to the current context. Kitab Al-Barzanji is a prayer, praise and narration of the history of the Prophet Muhammad which is recited with a rhythm or tone that is usually sung at the birth, circumcision, marriage and birthday of the Prophet Muhammad. which is mentioned in succession. The purpose of this research is 1) to examine and define the values ​​of faith education in the book of al Barzanji by Shaykh Ja'far al Barzanji 2) to examine the relevance of the values ​​of faith education in the book of al Barzanji by Shaykh Ja'far al Barzanji, research methods used. Qualitative research methods that are descriptive in nature follow the content analysis method (contents analysis The results of this research with the title values ​​of creed education in the book of al Barzanji by Shaykh Ja'far al Barzanji are: 1) belief in Allah subhana wata'ala 2) belief in mentioning Allah's name 3) belief in angels 4) belief in Apostles 5) creed about the concept of Nur Muhammad. These educational values ​​are a real reflection, especially in Islamic religious education.